Lyapunov-Based Finite Control Set Applied for Current Control of Grid-Connected Single-Phase Inverter Under Distorted Voltage Conditions - Augusto, Lucas Demetrius; de Oliveira Cota, Yuri; Alberto Torrico Altuna, Jose; Joaozinho Sguarezi Filho, Alfeu (IEEE access, 2025)
The growing use of renewable energy sources, primarily driven by climate change, necessitates synchronization with the electricity grid for the effective and reliable operation of single-phase inverters connected to the grid. However, when the system is subject to distortions and variations in the grid voltage, inverter control can be compromised. To mitigate these problems, this article presents a predictive controller based on the Finite Control Set Model Predictive Control, which utilizes a Lyapunov stability criterion in discrete time. The proposed controller operates on a single-phase inverter connected to the grid, aiming to enhance total harmonic distortion performance. The control system, which uses a phase-locked loop for synchronization, incorporates Lyapunov stability concepts to ensure that the controlled variables remain close to their reference values, even in the face of grid disturbances. Experimental tests show that the proposal is viable in practice, keeping total harmonic distortion below 5%, within the limits set by power quality standards. The controller's performance was evaluated under ideal and distorted grid conditions, and compared with a repetitive controller and a sliding mode controller combined with PI. Additionally, an analysis of parametric variations in the system was conducted. The results obtained show that the proposed strategy has superior performance in terms of harmonic suppression, validating its effectiveness and practical applicability.